GAMBARAN FAKTOR RISIKO PENYAKIT INFEKSI SALURAN PERNAFASAN AKUT (ISPA) DI WILAYAH KERJA PUSKESMAS MADUKARA 1 KABUPATEN BANJARNEGARA TAHUN 2021 - Bayu Suseno (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2021)
ARI cases in 2019 as of 7350 cases, decreased in 2020 to be 4.075 cases at the health center Madukara 1 Banjarnegara Regency. The purpose of this research is to know the description of the characteristics (gender and age), the density of dwelling rooms, ventilation of rooms, type of flooring rooms, room humidity, room lighting, room temperature, the ownership of the smoke hole, the type of fuel, the habit of opening the window of the room, the behavior when coughing and smoking habits. This research includes descriptive research with cross sectional method. Sampling technique with total sampling method that 37 respondents as the sample. The Data used in this research is primary data obtained from interviews and observations using questionnaires and secondary data from the health center. The results illustrate most of the respondents of the female gender (to 59.5%), aged above 24 years (29,7%), the density of dwelling rooms are not solid (62,2%), has a good ventilation (83,8%), has a type of floor rooms better (97,3%), has a room humidity is not good (59.5%), has room lighting is not good (to 59.5%), all of the respondents have the room temperature is better (100%), does not have the hole smoking (51,4%), use of firewood for cooking (70,3%), the habit of opening a window (62,2%) behavior when coughing left alone (75,5%), and habits of the family members who are smoking in the house (78,4%). This research is expected to society should further improve the knowledge about the health, so can emphasize the incidence of ARI and can increase the degree of health.